Why do we listen to music? A uses and gratifications analysis - Lonsdale, A.; North, Adrian (John Wiley & Sons Ltd., 2011)
Four ‘uses and gratifications’ studies investigated peoples’ reasons for listening to music(Study 1); and whether these reasons differ significantly from those associated with otherleisure activities (Study 2). In Study 3, an open-ended, qualitative research design wasused to investigate why people listen to music. In Study 4, a cross-sectional design wasused to investigate the possibility that people of different ages might listen to music fordifferent reasons. Findings showed that there are a number of reasons why participantslisten to music, comparison of which indicated that participants listen to music primarilyto manage/regulate their moods. Comparison with other leisure activities indicatedthat for the most part, listening to music was rated better than other leisure activitiesat serving an individual’s different needs. This versatility may explain why music is soimportant to people. Evidence was also found to suggest that the reasons for listeningto music may change as people grow older.